DEVELOPING UTTARAKHAND’S LOCAL FOOD MARKET: THE PARTICIPATION OF WOMEN FARMERS - Chamoli, Abhay; Pratap, Sumit; Uniyal, Naveen (The journal of contemporary issues in business and government, 2022)
Rural production systems and sociocultural structures are changing in Uttarakhand due to excessive male migration. These women who are left behind have seen observable changes in their lives, such as job loads, household responsibilities, and the methods of earning a living. The scaling of agricultural sector in the state is now totally dependent on the efforts put in by the women farmers. The current study is an attempt to bridge the gap between the current status of women farmers in the state and the challenges needed to be addressed for efficient local crop cultivation. Two villages from the Uttarkashi district were studied using a case- control design. The data collection method used was a quantitative approach, involving 80 women who responded to household surveys. Secondary data was also used to assess the current situation of local food farming in the state of Uttarakhand. The findings of the study reflected through the investigation of socio demographic standing of women farmers in the state, illustrated the lack of resources and unfair trade practices by traders in agro markets during the monsoon season. Whereas secondary data revealed uneven distribution of cold storage units among various districts of Uttarakhand.